Mannerisms and stereotypies in catatonia: beyond simple motor movements - Mahgoub, Yassir; Pathare, Aum; Hamlin, Dallas; Kindt, Hailey; Francis, Andrew (Frontiers in Psychiatry, 2024)
Background: Catatonia is a complex syndrome with prominent psychomotor, cognitive, and affective manifestations. Among the commonly described manifestations of catatonia are mannerisms and stereotypies. Kahlbaum, who coined the term catatonia, described several presentations of mannerisms and stereotypies as complex behaviors in his monograph. However, most of the subsequent psychiatric literature has described both phenomena in the context of simple motor movements or actions. Study Design or Method: We identified complex behavioral presentations of mannerisms and stereotypies described by Kahlbaum in his monograph. We summarize the development and use of mannerisms and stereotypies as psychiatric terminology since Kahlbaum, emphasizing the spectrum of behavior captured early in this usage. We list the inconsistent and interchangeable use of these terms in subsequent literature and describe recent examples of complex behavioral manifestations of mannerisms and stereotypies in the context of catatonia. Study Results: We propose a new framework for mannerisms and stereotypies that utilizes descriptive psychopathology factors in various normative references, the context of the behavior examined, and critical pathological processes identified in mannerisms and stereotypies to identify and describe complex manifestations of these phenomena. Conclusion: Catatonia continues to remain under-recognized and under-treated. Our current diagnostic tools can make mannerisms and stereotypies complex and challenging to recognize. We suggest defining stereotypies as non-contextual repetitive activities while mannerisms as non-contextual peculiarities of activities. Utilizing our proposed framework and definitions can improve the description, recognition, and treatment of catatonia.